Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.6520
|View full text |Cite
|
Sign up to set email alerts
|

FRI0226 Assessment of therapy adherence and treatment results in gout patients who attended schools for patients and in those who did not

Abstract: BackgroundGout is a poorly controlled disease despite the availability of effective treatment methods. One of the main reasons for its poor controll is patients’ low adherence to treatment, including due to insufficient knowledge of treatment principles.ObjectivesTo assess adherence to therapy and results of treatment in gout patients who attended schools for patients and in those who did not.MethodsAll patients with crystal-verified gout were interviewed and invited to attend School for gout pts. Totally 301 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…1 Gout is associated with significant disability, and consistent with an increase in prevalence, the World Health Organization 2010 Global Burden of Disease study demonstrated a doubling of disabilityadjusted life years for gout between 1990 and 2010. 4,5 The Queen Elizabeth Hospital (TQEH), located in the western suburbs of Adelaide, has a monthly gout clinic, which is run by three medical officers (rheumatologist, rheumatology registrar and basic physician trainee). This is usually due to inadequate education of the patient and/or their primary care physician regarding optimal gout treatment resulting in inappropriate ULT dosing, failure to treat to target serum urate, failure to prescribe flare prophylaxis, cessation of ULT during gout flares or because of worsening renal failure, and failure to appreciate that gout is a chronic condition requiring on-going medication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Gout is associated with significant disability, and consistent with an increase in prevalence, the World Health Organization 2010 Global Burden of Disease study demonstrated a doubling of disabilityadjusted life years for gout between 1990 and 2010. 4,5 The Queen Elizabeth Hospital (TQEH), located in the western suburbs of Adelaide, has a monthly gout clinic, which is run by three medical officers (rheumatologist, rheumatology registrar and basic physician trainee). This is usually due to inadequate education of the patient and/or their primary care physician regarding optimal gout treatment resulting in inappropriate ULT dosing, failure to treat to target serum urate, failure to prescribe flare prophylaxis, cessation of ULT during gout flares or because of worsening renal failure, and failure to appreciate that gout is a chronic condition requiring on-going medication.…”
mentioning
confidence: 99%
“…3 Several studies have demonstrated that regular follow-up for the management of gout leads to better disease control. 4,5 The Queen Elizabeth Hospital (TQEH), located in the western suburbs of Adelaide, has a monthly gout clinic, which is run by three medical officers (rheumatologist, rheumatology registrar and basic physician trainee). The treatment protocol follows current consensus guidelines 6-8 with a treat-to-target approach, which aims for a sustained target serum urate level of <0.36 mmol/L, or < 0.30 mmol/L for patients with complex disease and/or tophi.…”
mentioning
confidence: 99%
“…19,20 Knowledge was an essential factor because gout arthritis was a disease that is poorly controlled even though the available therapies are effective. 30 An experimental study found that patients who attended the "school for gout" had more knowledge, thereby increasing therapy adherence and the patient's quality of life. Regarding the explanation in the correlation of patient attitudes and behavior towards adherence to previous therapy, the correlation of knowledge has been investigated for several similar pharmacological therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Наш опыт обучающих мероприятий для пациентов позволяет согласиться, что подробная информация о подагре, в том числе о принципах ее лечения и самоконтроля, которую сообщает ревматолог, улучшает приверженность терапии и возможность достижения ее целей [39]. Аналогичные выводы были сделаны в ряде работ [40][41][42], в которых обучение пациентов проводилось медицинскими сестрами или фармакологами.…”
Section: «предоставление для оптимизации терапии средним медицинским unclassified
“…Аналогичные выводы были сделаны в ряде работ [40][41][42], в которых обучение пациентов проводилось медицинскими сестрами или фармакологами. Тем не менее метод получения пациентом информации имеет второстепенное значение [39], что подчеркивает условность рекомендации.…”
Section: «предоставление для оптимизации терапии средним медицинским unclassified